2009
DOI: 10.1097/jto.0b013e3181ae2844
|View full text |Cite
|
Sign up to set email alerts
|

Serum Osteopontin Levels are Highly Prognostic for Survival in Advanced Non-small Cell Lung Cancer: Results from JMTO LC 0004

Abstract: Consistent with the findings from SWOG 0003, low OPN serum levels were significantly associated with a favorable prognosis in the JMTO LC 0004. Additionally, high bFGF levels were associated with improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 19 publications
0
33
0
1
Order By: Relevance
“…Chambers et al (7) suggested its prognostic value and other groups also supported this idea (22,25). Although the association between OPN and prognosis has been investigated over several years, no definitive conclusion has been drawn.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Chambers et al (7) suggested its prognostic value and other groups also supported this idea (22,25). Although the association between OPN and prognosis has been investigated over several years, no definitive conclusion has been drawn.…”
Section: Discussionmentioning
confidence: 68%
“…1). Three of those studies were conducted in America (21-23), two in Japan (24,25) and one in Italy (19). All the studies had a minimum follow-up of 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…In their study the circulating osteopontin level is higher in stage III+IV than stage I+II. Latest research confirms that low osteopontin serum levels were significantly associated with a favorable prognosis in advanced NSCLC both in the Japanese patients (JMTO LC 0004) and the US population (SWOG study S0003 [23,24] . Our results suggested that osteopontin is critically involved in the aggressive progression of NSCLC.…”
Section: Discussionmentioning
confidence: 87%
“…The prognostic relevance of elevated OPN plasma levels has been demonstrated in the chemotherapy (18,19) and surgery of NSCLC (20), and also for tumor volume. Furthermore, there is strong evidence in the literature that GTV is a potential prognostic factor in conformal RT of NSCLC (13)(14)(15)(16)21).…”
Section: Discussionmentioning
confidence: 99%